The Media of Testimony - Jones, S. author. aut Link
X, 243 p.
Keywords: The Media of Testimony explores testimony relating to the Stasi in different cultural forms: autobiographical writing, memorial museums and documentary film. Combining theoretical models from diverse disciplines, it presents a new approach to the study of testimony, memory and mediation.